2009
DOI: 10.1103/physrevb.79.024427
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic interlayer coupling in Pt/Co multilayers with perpendicular anisotropy

Abstract: By using one ultrathin NiO layer to replace the Pt capping layer in the Co/Pt multilayer with perpendicular anisotropy, we present direct evidence for the existence of antiferromagnetic interlayer coupling between the Co layers through the Pt layers thicker than 24 Å. The NiO capping layers play two key roles in the observation of antiferromagnetic interlayer coupling. One is the manipulation of the coercivity of the Co layer in contact with the NiO layer, the other is the enhancement of the electron reflectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…The coercive fields measured for the samples grown on Pt are close to 200 Oe, i.e. similar to or slightly smaller than the values reported by other authors for these Co and Pt thicknesses [27][28][29]34]. Some studies have reported on the nonmonotonic/oscillatory variation of H c as a function of t Pt , which has been attributed to the oscillatory interlayer coupling in (Co / Pt) multilayers [27,28].…”
Section: Magnetic Properties Of (Co/pt) Stackingssupporting
confidence: 84%
“…The coercive fields measured for the samples grown on Pt are close to 200 Oe, i.e. similar to or slightly smaller than the values reported by other authors for these Co and Pt thicknesses [27][28][29]34]. Some studies have reported on the nonmonotonic/oscillatory variation of H c as a function of t Pt , which has been attributed to the oscillatory interlayer coupling in (Co / Pt) multilayers [27,28].…”
Section: Magnetic Properties Of (Co/pt) Stackingssupporting
confidence: 84%
“…Similar closed double square-shaped hysteresis loops are observed for antiferromagnetically coupled MHP between two ferromagnetic layers, 61 and for antiferromagnetically coupled multilayers, open or closed double square-shaped hysteresis loops can be obtained by tuning interlayer exchange coupling. 64,65 Therefore, we infer that closed double square-shaped hysteresis loops in Figure 4b are related to antiferromagnetic coupling between FM 1 and FM 2, which induces the magnetic moments of FM 1 to reverse at a small positive magnetic field.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…Even though the existence of AF coupling across the Pt spacer had been predicted theoretically [4], extensive studies on [Co/Pt] n multilayers with perpendicular anisotropy had just revealed the FM interlayer coupling [5][6][7]. Our recent investigations on the Co(4Å)/Pt(t PtÅ )/[Co(4Å)/Pt(6Å)] n multilayers with spin-valve configuration had reported the AF interlayer coupling through the Pt spacers [8][9][10][11][12]. The IEC oscillates as a function of Pt spacer thickness and repetition number at AF coupling background.…”
Section: Introductionmentioning
confidence: 93%